2022
DOI: 10.11591/ijeecs.v28.i2.pp1105-1116
|View full text |Cite
|
Sign up to set email alerts
|

A prediction model based machine learning algorithms with feature selection approaches over imbalanced dataset

Abstract: The educational sector faced many types of research in predicting student performance based on supervised and unsupervised machine learning algorithms. Most students' performance data are imbalanced, where the final classes are not equally represented. Besides the size of the dataset, this problem affects the model's prediction accuracy. In this paper, the Synthetic Minority Oversampling Technique (SMOTE) filter is applied to the dataset to find its effect on the model's accuracy. Four feature selection approa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 36 publications
0
1
0
Order By: Relevance
“…According to the study's [13] results, AP SMOTE had the highest yield when SMOTE and AP SMOTE were applied to an unbalanced data set. The study's findings showed that class data when students graduated that weren't balanced could be classified with greater accuracy, precision, and sensitivity when the SMOTE method was used [4], [11], [14], [15].…”
Section: Related Workmentioning
confidence: 99%
“…According to the study's [13] results, AP SMOTE had the highest yield when SMOTE and AP SMOTE were applied to an unbalanced data set. The study's findings showed that class data when students graduated that weren't balanced could be classified with greater accuracy, precision, and sensitivity when the SMOTE method was used [4], [11], [14], [15].…”
Section: Related Workmentioning
confidence: 99%
“…Under-sampling is done by reducing the amount of data from the majority class. Meanwhile, oversampling is done by increasing the data from the minority class [22], [23]. Another approach to dealing with the class unbalanced problem is to use stratified k-fold cross-validation (SCV) as an extension of the cross-validation technique.…”
Section: Introductionmentioning
confidence: 99%